Organizational Commitment and Identification of Engineers as a Function of Organizational Climate - Barth, R. (Relations industrielles / Industrial Relations, 1974)
This article examines the impact of organizational climate components upon engineers' commitment to, and identification with, their employing organizations. The application of multiple regression analysis indicates that a significant proportion of the variance of the dependent variables can be accounted for by organizational climate scores.